Social history of Mass Rapid Transit (MRT) in Singapore : the limited reach of MRTs, and the cost to Singapore’s development - Muhammad Asyraf Aliman (2016)
This paper focuses on the social history of the MRTs in Singapore. In particular, it argue that the overall benefits of the MRT, since the first stage of the North South Line was completed in 1987, have been overstated. This is largely due to the statements made by senior political figures or public servants. While this may be true to some extent, there were, and still are segments of the population, and certain geographical areas, that gain little from MRT developments since 1987. Residents in the suburbs, who are within the ideal 10-minute walk to an MRT station, are still find finding it inconvenient to take the MRTs for their daily commute to work or school. Besides that, certain neighbourhoods, or residential districts in the suburbs, are still pretty much cut off from direct access to an MRT station. It also means that a large number of the residents still rely on public buses or private transport for their daily commute to work, or when travelling to the city centre for the weekends. Given that their daily routine remained the same, with no effect